THE MEANING OF "CAREER CALLING" AMONG EMPLOYEES INVOLVED IN OUTREACH AT BNN IN JAMBI CITY - Ananda Putra Dwianugrah; Agung Iranda; Beny Rahim; Fadzlu (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2026)
The high rate of drug abuse in Indonesia indicates that this problem remains a serious one. One form of preventive effort undertaken by the Badan Narkotika Nasional is the implementation of narcotics counseling activities for the community. Naturally, there are personnel involved in carrying out this counseling. This study aims to describe the meaning of career calling among employees involved in counseling at the Badan Narkotika Nasional (BNN) in Jambi City. The method used is a qualitative approach with Interpretative Phenomenological Analysis (IPA) through in-depth interviews. The study involved three employees of the Badan Narkotika Nasional (BNN) in Jambi City as participants. The results identified seven main themes related to the meaning of career calling among employees involved in counseling: personal meaning, prosocial orientation, active participation, spiritual orientation, self-development, dedication, and providing benefits.